Central complex and mushroom bodies mediate novelty choice behavior in Drosophila. (March 2015) - Solanki, Narendra; Wolf, Reinhard; Heisenberg, Martin
Abstract Novelty choice, a visual paired-comparison task, for the fly Drosophila melanogaster is studied with severely restrained single animals in a flight simulator. The virtual environment simulates free flight for rotation in the horizontal plane. The behavior has three functional components: visual azimuth orientation, working memory, and pattern discrimination (perception). Here we study novelty choice in relation to its neural substrate in the brain and show that it requires the central complex and, in particular, the ring neurons of the ellipsoid body. Surprisingly, it also involves the mushroom bodies which are needed specifically in the comparison of patterns of different sizes.